2012
DOI: 10.4266/kjccm.2012.27.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pattern in Semi-Quantitative Sputum Cultures Based on Different Endotracheal Suction Techniques

Abstract: Background:The endotracheal suction was one of the critical requirements for severe neurosurgical patients in the prevention of the airway-obstruction, pneumonia, atelectasis, and so on. There were two types of suction methods, closed and open. In the literature, many reported the comparison of the two methods with variable factors, yet, it was still controversial. In this study, we compared the two types of endotracheal suction methods based on the pattern of the sputum cultivation, which was not discussed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Closed suction systems may be more effective for the ICU environment where ICU bed density is too high. In fact, some Korean studies showed closed suction system outperforms open suctioning in reducing infections [9][10][11]. In this study, there were no differences between the experimental and control catheters with respect to the incidence of hypoxia, hemodynamics, infection and ICU length of stay probably because both were closed-suction catheters.…”
contrasting
confidence: 71%
See 2 more Smart Citations
“…Closed suction systems may be more effective for the ICU environment where ICU bed density is too high. In fact, some Korean studies showed closed suction system outperforms open suctioning in reducing infections [9][10][11]. In this study, there were no differences between the experimental and control catheters with respect to the incidence of hypoxia, hemodynamics, infection and ICU length of stay probably because both were closed-suction catheters.…”
contrasting
confidence: 71%
“…Closed suctioning, backed by continuous supply of oxygen and positive end-expiratory pressure, is said to provide physiological stability and reduce the risk of nosocomial infection by keeping ventilator circuit closed. [6][7][8][9][10][11][12] However, its efficacy in preventing infections is still debated. [13,14] Newly developed closed-suction catheter (AceTrachcare, AceMedical Co., Republic of Korea) has dial-type pressure valve, located on the suction port, enables physicians to vary the level of suction pressure depending on the amount of secretions ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation